Collection and agro morphological characterization of Algerian accessions of lentil (Lens culinaris) - DJOUHER GAAD; MERIEM LAOUAR; AISSA ABDELGUERFI; FATIMA GABOUN (Biodiversitas Journal of Biological Diversity, 2018)
Gaad D, Laouar M, Gaboun F, Abdelguerfi A. 2018. Collection and agro morphological characterization of Algerian accessions of lentil (Lens culinaris). Biodiversitas 19: 183-193. Lentil is one of the important pulse crops in Algeria. The narrow genetic base of local cultivars and the disappearance of many local accessions contribute to the loss of lentil biodiversity. Therefore, collection, characterization and preservation of existing local accessions of lentils are important. Lentil accessions were collected across different agro-ecological zones of Algeria. From 10 regions (Departments), 15 villages were surveyed and 30 accessions were collected. Eighteen local accessions and 26 references collection have been used for agro morphological evaluation. The assessment was performed in two locations, sub-humid and semi-arid conditions, based on 12 quantitative characters. The result of variance analysis shows a significant effect of the interaction genotype x location for six quantitative traits. Three macrosperma Algerian accessions characterized by a high number of pod/plant, number of seed/plant and seed yield/plant were positioned on PCA1. The remaining Algerian accessions were positioned on PCA2 and were characterized by later flowering and maturity with high plant stature and height of the lowest pods. Hierarchical cluster analysis grouped the accessions into five distinct clusters independently of the accessions origins and revealed the distribution of Algerian accessions in all of the groups. This study will help breeders to better select accessions to be used in lentil breeding program.